Clark Street, North End, ca. 1880-1900 - Halliday Historic Photograph Company (Tufts Archival Research Center, 2005)
Street level view of Clark Street in Boston's North End. View is of the wooden frame buildings in the area. A child is seen in the foreground moving towards the photographer. On the right side of the image are two men walking on the sidewalk. 8 x 10 Photographs